When the Salt of the Earth Spoils - Rodriguez, Norman Simon (2025)
Jesus’ “salt of the earth” saying referred to salt losing its preservative properties and becoming susceptible to spoiling. It functioned as an idiom metaphorically representing the intelligence and maturity that the disciples were expected to display as exemplary preachers of the Gospel.
Keywords: Amputation; Hell; Luke 14:34–35; Mark 9:49–50; Matthew 5:13; salt of the earth